2012
DOI: 10.1111/j.1469-8749.2012.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in children before and after surgery for extratemporal lobe epilepsy

Abstract: ADHD Attention-deficit-hyperactivity disorder ASD Autism spectrum disorder DBD(NOS) disruptive disorders not otherwise specified DSM-IV Diagnostic and Statistical Manual of Mental Disorders (4th edition) ODD ⁄ CD oppositional defiant disorder/conduct disorder AIM To establish the rates and types of psychiatric disorder in children before and after surgery for extratemporal epilepsy. Relationships between psychiatric morbidity and demographic ⁄ clinical variables were examined.METHOD A retrospective case note r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Detection of common mental health problems in children with epilepsy, such as challenging behavior, ADHD, depression, and anxiety, warrants referral for standard evidence‐based treatments. The high rates found in epilepsy surgery patients indicate that this is a particularly vulnerable group, with rates of 52% to 83% in the studies reported here …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Detection of common mental health problems in children with epilepsy, such as challenging behavior, ADHD, depression, and anxiety, warrants referral for standard evidence‐based treatments. The high rates found in epilepsy surgery patients indicate that this is a particularly vulnerable group, with rates of 52% to 83% in the studies reported here …”
Section: Discussionmentioning
confidence: 56%
“…These difficulties often have a greater impact than the seizures themselves on health‐related quality of life but are often not identified or treated . In children undergoing epilepsy surgery, high rates of psychiatric comorbidity have been noted for both temporal lobe and extratemporal lobe cases …”
Section: Introductionmentioning
confidence: 99%
“…The neurological examination showed impairment in 25 children (31%): 22 presented with a motor impairment, with hemiplegia detected in 12, whilst three children presented with a visual field defect. Cognitive and psychopathological data for this population have been reported separately 10,11 …”
Section: Resultsmentioning
confidence: 99%
“…The proportion of seizure-free patients depends both on careful assessment for suitability and on the center performing the surgery. For patients with extratemporal focal-onset epilepsy, ie, with onset from areas of the brain other than the temporal lobe, the outcome is much less favorable 15. Again, the possibility of cognitive and behavioral/psychiatric adverse effects arising from the treatment, in this case surgery, need to be considered carefully, with the important difference that AEDs can be stopped but resective surgery cannot be reversed.…”
Section: Introductionmentioning
confidence: 99%